Human resource allocations in african agricultural research: revealing more of the story behind the regional trends - Beintema, Nienke M.; Rahija, Michael (International Food Policy Research Institute, 2011)
The aim of this paper is to provide an in-depth assessment of Sub-Saharan Africa's human resource capacity in agricultural research based on the wealth of detailed human capacity data collected through the Agricultural Science and Technology Indicators (ASTI) initiative. The region's overall agricultural R&D capacity has increased notably in recent years. In addition to this increase in absolute numbers, female participation improved in many countries and comparatively more researchers hold PhD and MSc degrees—although the share of those qualified to the BSc level increased for some countries during 2001-08. Nevertheless, many countries, especially some of the region's smallest, still have very low (and in a few cases declining) levels of human resource capacity. Agricultural research continues to be extremely fragmented, with most countries focusing on a large number of subsectors and wide range of crops, which remains the dominant subsector. Furthermore, after years of civil service recruitment freezes, many countries have disproportionately young and inexperienced teams of agricultural scientists in need of further training and mentoring, combined with disproportionately older senior scientists, many of whom are nearing retirement age. A further problem due to years of underfunding in many countries is the need to improve salary levels, conditions of service, facilities and equipment, and networking and career-development opportunities, which are fundamental to successfully attracting and retaining the kind of scientists needed to address the multitude of research challenges that await.